Ena/VASP Protein-Mediated Actin Polymerization Contributes to Naïve CD8+ T Cell Activation and Expansion by Promoting T Cell–APC Interactions In Vivo - Waldman, Monique M.; Rahkola, Jeremy T.; Sigler, Ashton L.; Chung, Jeffrey W.; Willett, Benjamin A. S.; Kedl, Ross M.; Friedman, Rachel S.; Jacobelli, Jordan (Frontiers in Immunology, 2022)
Naïve T cell activation in secondary lymphoid organs such as lymph nodes (LNs) occurs upon recognition of cognate antigen presented by antigen presenting cells (APCs). T cell activation requires cytoskeleton rearrangement and sustained interactions with APCs. Enabled/vasodilator-stimulated phosphoprotein (Ena/VASP) proteins are a family of cytoskeletal effector proteins responsible for actin polymerization and are frequently found at the leading edge of motile cells. Ena/VASP proteins have been implicated in motility and adhesion in various cell types, but their role in primary T cell interstitial motility and activation has not been explored. Our goal was to determine the contribution of Ena/VASP proteins to T cell–APC interactions, T cell activation, and T cell expansion in vivo. Our results showed that naïve T cells from Ena/VASP-deficient mice have a significant reduction in antigen-specific T cell accumulation following Listeria monocytogenes infection. The kinetics of T cell expansion impairment were further confirmed in Ena/VASP-deficient T cells stimulated via dendritic cell immunization. To investigate the cause of this T cell expansion defect, we analyzed T cell–APC interactions in vivo by two-photon microscopy and observed fewer Ena/VASP-deficient naïve T cells interacting with APCs in LNs during priming. We also determined that Ena/VASP-deficient T cells formed conjugates with significantly less actin polymerization at the T cell–APC synapse, and that these conjugates were less stable than their WT counterparts. Finally, we found that Ena/VASP-deficient T cells have less LFA-1 polarized to the T cell–APC synapse. Thus, we conclude that Ena/VASP proteins contribute to T cell actin remodeling during T cell–APC interactions, which promotes the initiation of stable T cell conjugates during APC scanning. Therefore, Ena/VASP proteins are required for efficient activation and expansion of T cells in vivo.